2022
DOI: 10.1021/acsomega.2c04576
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Photocatalytic Degradation of Tetracycline Using Heterostructured Cu2O–TiO2Nanotubes, Kinetics, and Toxicity Evaluation of Degraded Products on Cell Lines

Abstract: This study first reports on the tetracycline photodegradation with the synthesized heterostructured titanium oxide nanotubes coupled with cuprous oxide photocatalyst. The large surface area and more active sites on TiO 2 nanotubes with a reduced band gap (coupling of Cu 2 O) provide faster photodegradation of tetracycline under visible light conditions. Cytotoxicity experiments performed on the RAW 264.7 (mouse macrophage) and THP-1 (human monocytes) cell lines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…More recently, Sharma et al studied the photodegradation of tetracycline with visible light in the presence of titanium oxide nanotubes together with cuprous oxide photocatalysts. 52 The toxicity of the antibiotic and its photoproducts were checked on mouse macrophage and human monocyte cell lines, employing the MTT test to examine the viability of the cells. The results obtained by these authors confirmed that the photoproducts are not cytotoxic.…”
Section: Cytotoxicity Analysismentioning
confidence: 99%
“…More recently, Sharma et al studied the photodegradation of tetracycline with visible light in the presence of titanium oxide nanotubes together with cuprous oxide photocatalysts. 52 The toxicity of the antibiotic and its photoproducts were checked on mouse macrophage and human monocyte cell lines, employing the MTT test to examine the viability of the cells. The results obtained by these authors confirmed that the photoproducts are not cytotoxic.…”
Section: Cytotoxicity Analysismentioning
confidence: 99%
“…They concluded that modifying pH is an effective strategy to improve photocatalytic performance. Sharma et al [47] observed that the degradation rate of tetracycline with Cu 2 O-TiO 2 nanotube was complete under acidic, neutral, and alkaline conditions, and it is related to the adsorption of pollutants on the surface catalyst. The number of active sites on the catalyst surface increased, which, in turn, boosted the formation of main reactive species, such as electron-hole pairs or radical hydroxyl during the photo process.…”
Section: The Photocatalytic Activity Of Cu-doped Tio 2 221 Effect Of ...mentioning
confidence: 99%
“…Additionally, in the presence of an appropriate light source, electrons are excited from the VB to the CB of TiO 2 to create VB holes (positive charge carriers) and CB electrons (negative charge carriers). By scavenging the oxidizing species, these electron-hole pairs produce different reactive oxygen (ROS), further degrading the GBP on the surface of the Cu-TiO 2 [47].…”
Section: Catalytic Activity and Mechanism Of Gbp Degradation In The C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interfacial charge flow generates an internal electric field from TiO 2 to Cu 2 O due to localized regions of Cu 2 O and TiO 2 with surplus negative and positive charges. Finally, electron transfer from Cu 2 O to TiO 2 is facilitated by the p–n heterojunction, which promotes photocatalytic performance. Furthermore, solid supports, particularly carbonaceous materials, are increasingly used in photocatalytic reactions to prevent aggregation and protect semiconductor photostability . Also as electron mediators, they separate charge carriers in binary heterojunctions, enhancing photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%